EARLY PRENATAL DIAGNOSTICS OF INBORN HEART DISEASES OF FETUSES WITH NUCHAL TRANSLUCENCY - E.A. Shevchenko (Вопросы современной педиатрии, 2008)
The article represents an analysis of 38 events of inborn heart diseases of fetus with nuchal translucency, diagnosing on 11–16 weeks of pregnancy during consultative procedure. The spectrum of registered inborn heart diseases is represented by following nosologic forms: defect of interventricular partition, heart ectopy, atrioventricular canal, general arterial trunk, hypoplastic syndrome of the left sections of heart, fallot's tetrad, combination of defects of intracardiac partitions with diverticulum of ventricle. Frequency of registered inborn heart diseases and negative perinatal outcomes increased with the rise of thickness of nuchal translucency of fetus. transvaginal echocardiography with use of highly resolving ultra sonic equipment and new technology should be carried out in all cases of registration of widened nuchal translucency of fetus. It is decisive in improvement of diagnostics of inborn heart diseases, especially on early terms.Key words: inborn heart diseases, transvaginal echocardiography, prenatal diagnostics.